STUDENTS’ PERCEPTIONS TOWARD ANIMATED VIDEOS-BASED TEACHING MATERIALS (A STUDY CASE IN SEVENTH GRADE) - Apriati, Rahayu; Prastikawati, Entika Fani; Hawa, Faiza - (Universitas Muria Kudus, 2023)
Abstract:Technology has very important rules in our learning activities nowadays. It can be used for learning media in the EFL classroom. One of the blended learning media in the Merdeka Curriculum that can be used today is animated video. This study’s purpose is to investigate students’ perception of animated video-based teaching materials in seventh-grade students. This study of qualitative research with a survey design using an online questionnaire as an instrument. The result of this study shows students’ perception of animated video-based teaching materials in the seventh grade has fulfilled the Technology Acceptable Model (TAM). The results showed that 33 students agreed to animated video as a medium of learning. It showed the highest percentage of pronouncement of agreement. The data analyst found that students’ perception through animated videos has five components of TAM which showed the pronouncement of agreement. In addition, an animated video was effectively used as media for learning. In this case, the researcher found the research in the Junior High School of SMP Negeri 6 Semarang. In this study, it can be implied that animated video is available to use in learning English-based teaching materials.